Generalized K-Fibonacci Sequence of Q- Matrix - Kumar, Nand Kishor; Sahani, Suresh Kumar (Darul Yasin Al Sys, 2025)
This article explores the generalized K-Fibonacci sequence derived from matrices, extending the classical Fibonacci sequence to matrix representations. The properties and its applications are also described. The interplay of matrix algebra and generalized Fibonacci sequences offers insights into advanced sequence theory.